A Randomized, Controlled Trial of Levonorgestrel Vs. The Yuzpe Regimen as Emergency Contraception Method among Iranian Women. - Fatemeh Sadat Hoseini; Mohammad Eslami; Mohammed Abbasi; Fatemeh Noroozi Fashkhami; Soheila Besharati (Tehran University of Medical Sciences, 2013)
We aimed to compare acceptability of Levonorgestrel with the Yuzpe regimen among Iranian women based on their side-effects and resulting changes in the amount and pattern of menses.Five hundred twenty nine participants aged 15-49 having regular menses and one act of unprotected intercourse within 72 h were included in the double-blind, controlled trial in 2006-2007 and randomly assigned into LNG (n=263) and HD (n=266) groups, receiving Levonorgestrel 0.75 mg given 12 h apart and ethinyl estradiol 100 μg plus 0.5 mg Levonorgestrel 0.5 mg repeated after 12 h, respectively.The participants receiving Levonorgestrel experienced significantly lower side-effects in the case of nausea, vomiting, and dizziness (P0.05). No significant difference was observed between the efficiencies of the treatments.Significantly lower side-effects of Levonorgestrel can be considered as greater acceptability and translated to higher efficiency.